Decentralized Educational Administration: A Blockchain Model for Transparent Governance - Pasaribu, Hiras; Supriyanto, Didik; Widiatmoko, Adi (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. The current landscape of educational administration faces numerous challenges, including inefficiencies in governance, lack of transparency, and fragmented data management. These issues often result in delays in decision-making processes and decreased trust among stakeholders. With the increasing digitization of educational systems, decentralized technologies such as blockchain have emerged as potential solutions to improve transparency and streamline administrative functions. Purpose. This study aims to explore the implementation of a blockchain-based model for decentralized educational administration, focusing on enhancing transparency, data integrity, and governance efficiency. Method. The research employed a qualitative method through case studies of educational institutions integrating blockchain systems into their administrative processes. Data were collected via interviews with administrators, educators, and IT specialists, alongside document analysis of blockchain implementation frameworks. Results. The findings indicate that the blockchain model significantly improves transparency by providing an immutable ledger for record-keeping, enhancing accountability in decision-making processes, and allowing real-time access to administrative data. Additionally, the decentralized nature of blockchain reduces reliance on intermediaries, thereby increasing operational efficiency. Conclusion. In conclusion, the implementation of blockchain technology in educational administration presents a viable solution for transparent governance. However, challenges such as technical expertise, initial setup costs, and resistance to technological change need to be addressed for widespread adoption.